SUFISM COMPLETES SCIENCE:A CONTRIBUTION OF OSMAN NURI TOPBAŞ THOUGHT OF TURKEY - Sulaiman (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2022)
This article elaborates on the contribution of thought by Osman Nuri Topbaş in responding to modern science. Science has an inherent paradigm: nature has a law that has a fixed character and does not change, so it works mechanically and God is no longer involved in the next movement of nature. The consequence of this paradigm is that science is very quantitative and positivistic with empirical methods and mathematical logic. To respond to this paradigm, Topbaş is critical on the one hand but is appreciative of scientific findingson the other hand. His critical attitude is aimed at the establishment of scientists who deny metaphysical cosmology, while his appreciative attitudeis shown by making scientific data a reinforcement of the spiritual dimension of Sufism. The weakness of scientists must be refinedwith Sufism. Because Sufism perusesinside and reveals the secrets and wisdom of all universe phenomena. If science focuses on the material and visible world, Sufism guides human beingsto explore deeper into the realm of reality. This means that every discovery related to the material world is proof of the mightand dominanceof the Creator. From this fact, it can be said that science helps reveal the wonders of divine art to the surface, while Sufism directs humans to increasingly admire and appreciate the Creator.